Diagnóstico não invasivo da anemia fetal pela medida do pico de velocidade sistólica na dopplervelocimetria da artéria cerebral média Noninvasive fetal anemia diagnosis by middle cerebral artery peak systolic velocity waveform measurement - Marcos Roberto Taveira (Revista Brasileira de Ginecologia e Obstetrícia, 2004)
OBJETIVO: avaliar se existe associação entre a medida do pico de velocidade sistólica (PVS) na dopplervelocimetria da artéria cerebral média (ACM) e a concentração de hemoglobina fetal e determinar a sua capacidade diagnóstica. MÉTODOS: entre janeiro de 2000 e maio de 2003, 44 gestantes isoimunizadas foram submetidas a transfusão intra-uterina. Realizou-se estudo dopplervelocimétrico da ACM antes de cada transfusão fetal, sempre com intervalo inferior a 3 horas, antecedendo o procedimento. O PVS da ACM foi considerado alterado quando seu valor era superior a 1,5 múltiplo da mediana para a respectiva idade gestacional. A concentração de hemoglobina do cordão foi aferida antes de se iniciar a infusão de sangue, realizada no Hemocue® (B-Hemoglobin Photometer Hemocue AB; Angelholm, Sweden). O estudo estatístico foi feito pelo teste do chi2 e também foram calculados os valores de sensibilidade, especificidade, valores preditivos positivo e negativo. RESULTADOS: foram realizados 83 procedimentos, sendo que em 33 a hemoglobina fetal era inferior a 10,0 g/dL. Houve associação significativa entre as variáveis estudadas, p<0,001. Fetos com hemoglobina menor ou igual a 10 g/dL apresentaram aumento significativo na medida do PVS na ACM, com valores superiores a 1,5 múltiplo da mediana. O PVS na ACM apresentou sensibilidade de 75,7% para a detecção de hemoglobina do cordão menor ou igual a 10 g/dL. CONCLUSÃO: o pico de velocidade sistólica na artéria cerebral média pode ser utilizado como método complementar no diagnóstico da anemia fetal. PURPOSE: to assess the correlation between middle cerebral artery peak systolic velocity and umbilical cord blood hemoglobin concentration and to determine its diagnostic value. PATIENTS AND METHODS: a cross-sectional prospective study was performed from January 2000 to May 2003. Forty-four isoimmunized pregnant women underwent a protocol for the identification of fetal hemolysis. When intrauterine transfusions were indicated, the umbilical cord blood hemoglobin concentration was measured at the beginning of the procedure. Each intrauterine transfusion preceded by Doppler velocimetry of the middle cerebral artery was regarded as one case, summing up eighty-three procedures. In all cases, the middle cerebral artery Doppler examinations were performed within the three hours preceding fetal blood sample collection. The systolic velocity peak was recorded and considered abnormal when its value was above 1.5 times the median for the corresponding gestational age. Hemocue® (B-Hemoglobin Photometer Hemocue AB; Angelholm, Sweden) was the device used to measure fetal hemoglobin concentration. The relationship between middle cerebral artery peak systolic velocity and cord blood hemoglobin was obtained by the chi2 test, considered significant at p<0.05. RESULTS: in thirty-three cases the cord blood hemoglobin concentration was below 10.0 g/dL. There was a strong correlation between the two measured variables (p<0.001). The middle cerebral artery peak systolic velocity with values above 1.5 times the median was associated with cord blood hemoglobin concentration below 10 g/mL (p<0,001). The sensitivity of an increased middle cerebral artery peak systolic velocity was 75.8% for the detection of a cord blood hemoglobin level of 10 g/dL or lower. CONCLUSION: the middle cerebral artery peak systolic velocity can be used as a noninvasive method for the diagnosis of fetal anemia.